Whoever has not this Name but one in the Sunnahs of Abi Dawood and the Imam Al-Tirmidhi collector - collection and study- - Ahmed , Othman (Islamic Sciences Journal, 2023)
Praise be to Allah , the Lord of the worlds, who created everything and was well appreciated. I witness that there is no God but Allah alone and has no partner, a testimony that I have saved for the question of a denier and a denier, I supplemented it with a testimony that Muhammad is his worshipper and messenger, the best prophet and the truest harbinger, may Allah bless him and upon all his companions And after: The Prophet’s Sunnah is the second source of legislation - after the Book of Allah Almighty - for it is one of the fundamentals of the religion and a basic evidence of rulings. Scholars have taken care from an early period of writing books that deal with the narrators of his hadith and the transmission of his news, may Allah bless him and grant him peace. When the six books were written in the hadith, then Hafiz Ibn Asakir al-Dimashqi, who was the first author among the sheikhs of the owners of the six books had written , a book entitled (the dictionary that includes mentioning the sheikhs of the imams nobility) Then scientists continued to write and take care of those books . This modest research came as a step on the Sunnah of our advanced scholars. Encouraged me to it, and drew me to it. It is what I have stood for in a book entitled: (Mention the name of all my companions who narrated an order or prohibition on the authority of the Messenger of Allah, and after him from the followers and others who have no brother His name corresponds to the transmission of hadith from all regions) by Abu Al-Fath Muhammad bin Al-Hussein bin Ahmed bin Abdullah bin Buraidah Al-Mawsili Al-Azdi (d.374 AH) and after trusting Allah alone without a partner, I laid out my plan and method for working in this research, so I divided my research into an introduction and mentioned the importance of The topic and the aim of the study, then the research consisted of twenty-seven topics, then a conclusion and a list of sources